2013
DOI: 10.2337/db13-0345
|View full text |Cite
|
Sign up to set email alerts
|

Teplizumab (Anti-CD3 mAb) Treatment Preserves C-Peptide Responses in Patients With New-Onset Type 1 Diabetes in a Randomized Controlled Trial

Abstract: Trials of immune therapies in new-onset type 1 diabetes (T1D) have shown success, but not all subjects respond, and the duration of response is limited. Our aim was to determine whether two courses of teplizumab, an Fc receptor–nonbinding anti-CD3 monoclonal antibody, reduces the decline in C-peptide levels in patients with T1D 2 years after disease onset. We also set out to identify characteristics of responders. We treated 52 subjects with new-onset T1D with teplizumab for 2 weeks at diagnosis and after 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
327
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 352 publications
(343 citation statements)
references
References 32 publications
13
327
0
3
Order By: Relevance
“…We posit that one successful approach would be to augment the Treg pool with an ex vivo expanded Treg infusion, while debulking the Teff population with drugs such as anti-CD3 monoclonal antibody or LFA3-Ig, which have already shown some promise in new onset T1D trials [11,12].…”
Section: Combination Therapymentioning
confidence: 99%
“…We posit that one successful approach would be to augment the Treg pool with an ex vivo expanded Treg infusion, while debulking the Teff population with drugs such as anti-CD3 monoclonal antibody or LFA3-Ig, which have already shown some promise in new onset T1D trials [11,12].…”
Section: Combination Therapymentioning
confidence: 99%
“…A number of interventions used in recent-onset T1D have shown transient symptoms related to cytokine release (62). B: In that same study, retention of b-cell function for 2 years in responders, whereas nonresponders were identical to the comparison control group.…”
Section: Failure To Distinguish Transient Symptoms From Serious Advermentioning
confidence: 91%
“…Despite suggestions of benefit from GAD-Alum vaccine in a phase 2 study (1), further studies, including two large phase 3 trials, showed no effect (2)(3)(4). Phase 3 trials with Anti-CD3 monoclonal antibodies failed to achieve their primary outcome (5-7), despite very promising results from multiple phase 2 trials (8)(9)(10)(11)(12)(13). The conflicting Anti-CD3 data may be explained by unfortunate changes in design (5) or dose (6,7) in phase 3 (14).…”
Section: Struggles With Clinical Translation Of Immune Intervention Tmentioning
confidence: 99%
“…But again, one could argue that no one consumes or injects glucagon routinely and that the GST response may not be the clinically most relevant parameter. Moreover, a multitude of recent clinical trials of immune interventions in recent-onset type 1 diabetes have been reported and almost all have used the MMTT as the primary outcome measure (1)(2)(3)(4)(6)(7)(8)(9)12,13,(15)(16)(17)(18)(19)(20). Each reader will have to make his or her own decision on what is the best test, as data comparing the two stimuli are not available from other large trials.…”
Section: Struggles With Clinical Translation Of Immune Intervention Tmentioning
confidence: 99%